2019
DOI: 10.32635/2176-9745.rbc.2018v64n3.43
|View full text |Cite
|
Sign up to set email alerts
|

Terapia Nutricional de Pacientes com Câncer Infantojuvenil submetidos a Transplante de Células-Tronco Hematopoiéticas

Abstract: Introdução: O estado nutricional é fortemente afetado pelo processo de transplante de células-tronco hematopoiéticas (TCTH). Os distúrbios nutricionais em pacientes TCTH são comuns e  são consequência da doença primária, da terapia de citorredução realizada durante o regime de condicionamento e das suas complicações, como as infecções, enterocolite neutropênica, doença do enxerto contra o hospedeiro, entre outras. Objetivo: Realizar uma revisão narrativa com base nos principais estudos e posicionamento de expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…However, in clinical practice, it is sometimes the best available option for patients with a compromised gastrointestinal tract and other clinical complications. These observations underscore the importance of new studies comparing ETF and PN, as suggested by Bicakli et al 14 and also by Garófolo and Nakamura 17 ; these authors note that there is little evidence to support nutritional recommendations and nutrition therapy for pediatric patients submitted to HSCT, but encourage the use of ETF based on their review of the literature and practical experience 17 . In the present study, patients who received ETF had shorter hospital stays, even when compared to patients on a total oral diet.…”
Section: Discussionmentioning
confidence: 91%
“…However, in clinical practice, it is sometimes the best available option for patients with a compromised gastrointestinal tract and other clinical complications. These observations underscore the importance of new studies comparing ETF and PN, as suggested by Bicakli et al 14 and also by Garófolo and Nakamura 17 ; these authors note that there is little evidence to support nutritional recommendations and nutrition therapy for pediatric patients submitted to HSCT, but encourage the use of ETF based on their review of the literature and practical experience 17 . In the present study, patients who received ETF had shorter hospital stays, even when compared to patients on a total oral diet.…”
Section: Discussionmentioning
confidence: 91%
“…Além disso, em alguns casos específicos é preconizado o uso de transplante de células tronco hematopoiéticas e variam conforme o diagnóstico, refratariedade, recidiva e remissão da doença oncológica. Estes protocolos estimam a recuperação do organismo do paciente prevendo um período livre de tratamento antes do início de cada novo ciclo de quimioterapia [30,31].…”
Section: Terapia Antineoplásicaunclassified